Peran Mahasiswa Keperawatan dalam Pemenuhan Kebutuhan Spiritual Selama Praktik - Situmeang, Andra Eunike Vieira Bianca; Hutapea, Lyna M (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the extent to which student nurses provide spiritual nursing care to clients in private hospitals. The method used is descriptive quantitative. The research results show that the role of nursing students in fulfilling the spiritual needs of patients is very often (16.7%), often (52.8%), rarely (27.8%), and never (2.8%). In conclusion, the role of nursing students in fulfilling spiritual needs often falls into the increasing category. Keywords: Spiritual Needs, Nursing Students, Clinical Practice